2020
DOI: 10.2147/idr.s233612
|View full text |Cite
|
Sign up to set email alerts
|

<p>Phenotypic and Genotypic Assessment of Antibiotic Resistance and Genotyping of <em>vacA</em>, <em>cagA</em>, <em>iceA</em>, <em>oipA</em>, <em>cagE</em>, and <em>babA2</em> Alleles of <em>Helicobacter pylori</em> Bacteria Isolated from Raw Meat</p>

Abstract: Background: Foodstuffs with animal origins, particularly meat, are likely reservoirs of Helicobacter pylori. Purpose: An existing survey was accompanied to assess phenotypic and genotypic profiles of antibiotic resistance and genotyping of vacA, cagA, cagE, iceA, oipA, and babA2 alleles amongst the H. pylori bacteria recovered from raw meat. Methods: Six-hundred raw meat samples were collected and cultured. H. pylori isolates were tested using disk diffusion and PCR identification of antibiotic resistance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Similar findings have been reported from Iran [32,33], Bulgaria [34] and Egypt [35]. High prescription of antibiotic agents caused severe increase in the levels of antibiotic resistant-bacteria other than antibiotic residues [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been reported from Iran [32,33], Bulgaria [34] and Egypt [35]. High prescription of antibiotic agents caused severe increase in the levels of antibiotic resistant-bacteria other than antibiotic residues [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 81%
“…The growingincidence of foodborne diseases in variousworld sites has been related to increasedraw food consumption [11,[19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that C. sinousa extract (10%) could improve the sensory score and extend the shelf-life of Pacific white shrimp up to 20 days. According to the high prevalence of food-borne pathogens in Iran [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], application of C. sinousa extract as a natural preservative has been suggested in future investigations.…”
Section: Discussionmentioning
confidence: 99%